(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper presents a sentence-by-sentence linguistic analysis of the short narrative “Unity” from the book by Utkir Hoshimov “Daftar hoshiyasidagi bitiklar” translated by F. Bekmurodova. Drawing on key theories in pragmatics and syntax, it explores how language use—through tense, clause structure, deixis, implicature, and speech acts—constructs moral and ideological meaning. The study contrasts two scenes: one depicting human silence during the Stalinist repressions of 1937, and another portraying a group of monkeys defending one of their own. The analysis shows how grammatical precision and pragmatic nuance converge to convey themes of complicity, courage, and collective action. Ultimately, the narrative offers a powerful commentary on the human condition by suggesting that animals, not people, embody true unity.